Beiträge zur deutschen Grammatik Gesammelte Schriften von Tilman N. Höhle, 2. durchgesehene Auflage - Müller, Stefan; Höhle, Tilman N.; Reis, Marga; Richter, Frank (Classics in Linguistics, 2019)
This volume contains the complete collection of published and unpublished work on German grammar by Tilman N. Höhle. It consists of two parts. The first part is Topologische Felder, a book-length manuscript that was written in 1983 but was never finished nor published. It is a careful examination of the topological properties of German sentences, including a discussion of typological assumptions. The second part assembles all other published and unpublished papers by Höhle on German grammar. All of these papers were highly influential in German linguistics, in theoretical linguistics in general, and in a specific variant of theoretical linguistics, Head-Driven Phrase Structure Grammar. Topics covered are clause structure, constituent order, (verum) focus, word structure, the relationship between relative pronouns and verbs in V2, and the foundations of a theory of phonology in constraint-based grammar. This book is a revised version of http://langsci-press.org/catalog/book/149